Valorização da cinza industrial na remoção da dipirona sódica e estudo de sua reatividade em matriz de cimento Portland - Lascosk, Luiza (2022)
This study aimed to evaluate the use of industrial ash from eucalyptus chips in the biosorption of sodium dipyrone and subsequent study of the reactivity of the ash after biosorption (AAB) in Portland cement matrix. Biosorption assays were carried out in batches, evaluating the effects of operating conditions: pH, temperature, agitation and contact time, in addition to kinetic and thermodynamic parameters. The biosorbent, ash which is an abundant industrial waste, was characterized from the point of zero charge (PCZ), the determination of the average diameter of the particles and the analysis of the surface area of the biosorbent (BET). For comparison purposes, before and after the biosorption process, scanning electron microscopy (SEM), energy dispersive x-ray spectroscopy (EDS), Fourier transform infrared spectrometry (FTIR) were performed. Regarding the study of the reactivity in Portland cement matrix (industrial ash after dipyrone biosorption) on the properties of mortars, the ash was characterized through analyzes of specific mass, moisture, loss on fire and X-ray fluorescence. Ash pozzolanicity was studied by X-ray diffractometry (XRD), modified Chapelle, pozzolanic activity index with lime and performance index with cement. While for the study of cement pastes, analyzes of compressive strength, tensile strength by diametrical compression, immersion absorption and determination of the specific mass were performed. Biosorption performed better at 25 ºC, 130 rpm, without pH adjustment, with 93.23% of commercial dipyrone removed in aqueous solution. The pseudo-second order kinetic model fitted better to the experimental data. The process was characterized as exothermic and spontaneous from the parameters of enthalpy and Gibbs free energy, respectively, indicating that the biosorption is favorable from a thermodynamic point of view. The activation energy of 24.017 kJ/mol showed that the removal occurs by physisorption and the positive value found for entropy (ΔS° = 59.07 J/K.mol) indicates an increase in randomness at the solid/solution interface. The chemical composition of ash and AAB, determined by XRF analysis, showed a predominance of calcium oxide (CaO) followed by magnesium oxide (MgO). XRD analysis showed the presence of calcite, kaolinite, magnetite, quartz, iron oxide and calcium oxide, without the presence of amorphous halo. In tests that evaluated the reactivity in Portland cement matrix of ash and AAB, such as minimum strength in ID with cement and minimum strength in IAP with lime, they did not reach the minimum limit to obtain pozzolanic material classification. However, in the study of the filer effect, using cement pastes, both materials showed favorable results in the partial replacement of cement in the composition of mortars, with the replacement of 10% or 15% being the best replacements. Fitting in the context of a circular economy, with the reuse of boiler ash residue in the biosorption of the drug sodium dipyrone and later in the replacement of cement in the composition of the mortars, due to the filer effect it presented.